2010
DOI: 10.1007/s11548-010-0535-3
|View full text |Cite
|
Sign up to set email alerts
|

New prototype neuronavigation system based on preoperative imaging and intraoperative freehand ultrasound: system description and validation

Abstract: The components and functionality of a new prototype system are described and its precision and accuracy evaluated. It was found to have an accuracy similar to other comparable systems in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 71 publications
3
26
0
1
Order By: Relevance
“…Results presented by Kowal et al 41 are comparable with ours in terms of accuracy performances, but worse (one order of magnitude) in terms of precision. Recently, Mercier et al 4 reported 0.64 mm as mean value for the point reconstruction accuracy. Chen et al, 42 who performed beam thickness correction in the calibration, 21 reached a similar value (0.66 mm as mean accuracy).…”
Section: Discussionmentioning
confidence: 99%
“…Results presented by Kowal et al 41 are comparable with ours in terms of accuracy performances, but worse (one order of magnitude) in terms of precision. Recently, Mercier et al 4 reported 0.64 mm as mean value for the point reconstruction accuracy. Chen et al, 42 who performed beam thickness correction in the calibration, 21 reached a similar value (0.66 mm as mean accuracy).…”
Section: Discussionmentioning
confidence: 99%
“…IOUS helped to locate and show the affected areas detected with ECoG by real-time imaging. We performed IOUS using aLogiq p6 (GE Healthcare, Washington) and a linear transducer (7)(8)(9)(10)(11). The probe was placed on the frontal pole and displayed the abnormal frontal lobe parenchyma with homogeneously hyperechoic expanded gyri (Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…For spinal neurosurgery we can also add measures of amount of residual tumor detected [15] and rates of various complications [16]. Other complications not mentioned in the above audits or registry studies are: Vascular injury including blood loss or (rare) iatrogenic thoracic aortic injury cases [17,18]; radiation injury [19].…”
Section: Review Of Success Criteramentioning
confidence: 99%
“…Ultrasound imaging also has potential to be used in spinal navigation [15,34]. Kolstad et al outline the problem of 2D ultrasonography in the positioning of the operating instruments since the orientation of the probe must be taken into account to estimate the depth of the lesion, whereas 3D-US (where an image volume is generated by tilting or translating the probe) is able to locate the probe in 3D space.…”
Section: Review Of Success Criteramentioning
confidence: 99%